If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -85 + -12x = -89 + -6x Solving -85 + -12x = -89 + -6x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '6x' to each side of the equation. -85 + -12x + 6x = -89 + -6x + 6x Combine like terms: -12x + 6x = -6x -85 + -6x = -89 + -6x + 6x Combine like terms: -6x + 6x = 0 -85 + -6x = -89 + 0 -85 + -6x = -89 Add '85' to each side of the equation. -85 + 85 + -6x = -89 + 85 Combine like terms: -85 + 85 = 0 0 + -6x = -89 + 85 -6x = -89 + 85 Combine like terms: -89 + 85 = -4 -6x = -4 Divide each side by '-6'. x = 0.6666666667 Simplifying x = 0.6666666667
| kx^2-14x+49=0 | | 2y+3y+13=23 | | -16=-6-5z | | h(t)=-16t^2+192t+90 | | 27+35+23=180 | | 2z-13=27 | | -40=-5pm | | 23-3w=80 | | 240x^3+540x^2-2160x=0 | | 8x-22=3(3x+21)-x | | 1492=75 | | -7x-66=-2x+54 | | 7a-2=40 | | .8x+5=0.2(40+x) | | 4ln5/1-ln5 | | 42=3x+6 | | 240x^2+675x-2160=0 | | (4x+5)+x=360 | | X/6-1=-6 | | (4x+5)+c=360 | | 4x/x=30 | | -5(6x-2+6)=30 | | (4x+5)+x=180 | | 3(x-5)-2(2x+1)=-8 | | l+15.2=-4.2 | | x^3+x^2-125d^3-25d^2= | | 240x^3+675x^2-2160x=0 | | -12x-141=-3x+102 | | 5*2-8*3+9= | | 10-4y=20 | | 4x-4y=y^2 | | -101-x=12x+55 |